Legal Protection for Film Copyright Holders Against Illegal Downloading and Streaming Activities on the Internet - Anugrah, Muhammad (Indonesia Law Reform Journal, 2023)
Copyright holders have exclusive rights to their creations or work. Illegal downloading and streaming of movies can be detrimental to copyright holders and countries. Therefore, perpetrators can be subject to criminal and civil sanctions. This study aims to: (1) determine the protection for the Moral Rights and Economic Rights of film creators or Copyright Holders from illegal downloading and streaming of films on the Internet and (2) determine how the law should regulate the rights of creators from illegal downloading and streaming activities to provide legal protection. The type of research used in this study is normative juridical by using data collection techniques through literature studies. The results show that: (1) the protection of Economic Rights and Moral Rights of film copyright is still lacking in providing legal protection because sanctions for violators of Moral Rights have not been regulated in the Copyright Law (2) the Copyright Law has regulated legal steps that Copyright Holders can take to obtain legal protection in the field of Copyright through mediation, criminal complaints, claims for compensation, and reports on the closure of content and access rights